Surgery with disc prosthesis versus rehabilitation in patients with low back pain and degenerative disc: two year follow-up of randomised study - Hellum, Christian (BMJ Publishing Group Ltd., 2011)
Objective To compare the efficacy of surgery with disc prosthesis versus non-surgical treatment for patients with chronic low back pain. Design A prospective randomised multicentre study. Setting Five university hospitals in Norway. Participants 173 patients with a history of low back pain for at least one year, Oswestry disability index of at least 30 points, and degenerative changes in one or two lower lumbar spine levels (86 patients randomised to surgery). Patients were treated from April 2004 to September 2007. Interventions Surgery with disc prosthesis or outpatient multidisciplinary rehabilitation for 12-15 days. Main outcome measures The primary outcome measure was the score on the Oswestry disability index after two years. Secondary outcome measures were low back pain, satisfaction with life (SF-36 and EuroQol EQ-5D), Hopkins symptom check list (HSCL-25), fear avoidance beliefs (FABQ), self efficacy beliefs for pain, work status, and patients’ satisfaction and drug use. A blinded independent observer evaluated scores on the back performance scale and Prolo scale at two year follow-up. Results The study was powered to detect a difference of 10 points on the Oswestry disability index between the groups at two years. At two years there was a mean difference of −8.4 points (95% confidence interval −13.2 to −3.6) in favour of surgery. In the analysis of prespecified secondary outcomes, there were significant differences in favour of surgery for low back pain (mean difference −12.2, −21.3 to −3.1), patients’ satisfaction (63% (n=46) v 39% (n=26)), SF-36 physical component score (mean difference 5.8, 2.5 to 9.1), self efficacy for pain (mean difference 1.0, 0.2 to 1.9), and the Prolo scale (mean difference 0.9, 0.1 to 1.6). There were no significant differences in return to work, SF-36 mental component score, EQ-5D, fear avoidance beliefs, Hopkins symptom check list, drug use, and the back performance scale. One serious complication of leg amputation occurred during surgical revision of a polyethylene dislodgement. The drop-out rate was 20% (34) and the crossover rate was 6% (5). Conclusions Surgical intervention with disc prosthesis for chronic low back pain resulted in a significantly greater improvement in the Oswestry score compared with rehabilitation, but this improvement did not clearly exceed the prespecified minimally important clinical difference between groups of 10 points, and the data are consistent with a wide range of differences between the groups, including values well below 10 points. The potential risks of surgery and the substantial amount of improvement experienced by a sizeable proportion of the rehabilitation group also have to be incorporated into overall decision making. Trial registration NCT 00394732.